Proceedings of the Twenty-First Annual ACM-SIAM Symposium on Discrete Algorithms 2010
DOI: 10.1137/1.9781611973075.134
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition for the Mixing Time of the Glauber Dynamics for Coloring Regular Trees

Abstract: We prove that the mixing time of the Glauber dynamics for random k-colorings of the complete tree with branching factor b undergoes a phase transition at k = b(1+o b (1))/ ln b. Our main result shows nearly sharp bounds on the mixing time of the dynamics on the complete tree with n vertices for k = Cb/ ln b colors with constant C. For C ≥ 1 we prove the mixing time is O(n 1+o b (1) ln 2 n). On the other side, for C < 1 the mixing time experiences a slowing down, in particular, we prove it is O(n 1/C+o b (1) ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…For planar graphs with maximum degree Δ, Hayes et al [10] were able to achieve polynomial mixing time for k ≪Δ, in particular, they showed polynomial mixing time when k > 100Δ/log Δ. More recently, Tetali et al [24] have shown that on the complete tree the mixing time of the Glauber dynamics has a phase transition at k ≈︁Δ /log Δ.…”
Section: Introductionmentioning
confidence: 99%
“…For planar graphs with maximum degree Δ, Hayes et al [10] were able to achieve polynomial mixing time for k ≪Δ, in particular, they showed polynomial mixing time when k > 100Δ/log Δ. More recently, Tetali et al [24] have shown that on the complete tree the mixing time of the Glauber dynamics has a phase transition at k ≈︁Δ /log Δ.…”
Section: Introductionmentioning
confidence: 99%
“…They also generalized the setting for the upper bounds to nonregular trees. Very recently, Tetali, Vera, Vigoda, and Yang [20] have pinned down the constant in the exponent and located the phase transition between "nearly linear" (i.e, n 1+o(b) ) and superlinear mixing time.…”
Section: Introductionmentioning
confidence: 99%
“…This was resolved recently by Lucier and Molloy and Goldberg et al who showed that for constant Δ and constant k , the mixing time is polynomial. (See also for further improvements regarding the mixing time of the Glauber dynamics on the complete tree. )…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to the initial publication of this work, the threshold for extremality of the free measure in the tree was established at k=(Δ/lnΔ)(1+o(1)) . More recent work of Tetali et al shows that the mixing time of the Glauber dynamics on the complete tree undergoes a phase transition at (up to first order terms) the reconstruction threshold. More precisely, for constant C > 0, for k=CΔ/lnΔ, on the n ‐vertex (Δ1)‐ary tree, they prove the mixing time is O(n1+o(1)lnn) for C1 and Ω(n1/Co(1)) for C < 1.…”
Section: Introductionmentioning
confidence: 94%